Psychology in Education and Health. Proceedings of the III Leipzig-Evora Scientific Meeting in Psychology - Edgar Galindo (2019)
The phenomena of achievement motivation is one of the most important among studied by psychology as far as its study approaches of scientists to the answer to the question about motivation forces of human behavior and activity. Motivation for achievement consists of two main components - adaptive and transcendent vectors. Based on the empirical studies carried out, the authors obtained results that became the basis for the assumption that the motivation of achievement among people who are conditionally called healthy is fundamentally different from the motivation of achievement among people with mental pathology. There is a non-linear link between mental health, mental disorders and adaptation, transcendence. Mental health requires a balance of these two components of the motivational sphere.